2011
DOI: 10.1534/genetics.110.121996
|View full text |Cite
|
Sign up to set email alerts
|

HID-1, a New Component of the Peptidergic Signaling Pathway

Abstract: hid-1 was originally identified as a Caenorhabditis elegans gene encoding a novel conserved protein that regulates the decision to enter into the enduring dauer larval stage. We isolated a novel allele of hid-1 in a forward genetic screen for mutants mislocalizing RBF-1 rabphilin, a RAB-27 effector. Here we demonstrate that HID-1 functions in the nervous system to regulate neuromuscular signaling and in the intestine to regulate the defecation motor program. We further show that a conserved N-terminal myristoy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(49 citation statements)
references
References 106 publications
4
45
0
Order By: Relevance
“…Subsequently, hid-1 has been isolated by a genetic screen for mutants mislocalizing rabphilin (RBF-1 in C. elegans ), an effector of RAB-27 that is involved in SG exocytosis (Mesa et al, 2011). The Hid1 gene encodes a highly conserved protein (HID-1) that has homologs in Drosophila melanogaster , mouse, and Homo sapiens , but not in budding yeast.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, hid-1 has been isolated by a genetic screen for mutants mislocalizing rabphilin (RBF-1 in C. elegans ), an effector of RAB-27 that is involved in SG exocytosis (Mesa et al, 2011). The Hid1 gene encodes a highly conserved protein (HID-1) that has homologs in Drosophila melanogaster , mouse, and Homo sapiens , but not in budding yeast.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the 59 importance of the signaling molecules released by dense-core vesicles, surprisingly little is known 60 about how dense-core vesicles are generated and acquire their proper cargos (1-4). 61 Dense-core vesicles originate at the trans-Golgi network, but it is unclear how their 62 compartmental identity is established and how cargos are correctly sorted into nascent dense-63 core vesicles. After budding from the trans-Golgi, immature dense-core vesicles undergo a poorly 64 defined maturation process that involves homotypic vesicle fusion, peptide processing, and the 5 Molecular mechanisms of dense-core vesicle biogenesis are poorly understood largely 76 because few proteins have been identified that function in this process.…”
mentioning
confidence: 99%
“…23,25 By tissue specifically expressing HID-1 in a hid-1 null background, either in the gut (under a ges-1 promoter) or in the nervous system (under a rab-3 promoter), we demonstrated that hid-1 is only needed in the nervous system to mediate pumping inhibition. 19 We next searched for the neuronal subtype in which hid-1 mediates the effect of CO 2 on the pharynx.…”
Section: Hid-1 Function Is Requiredmentioning
confidence: 87%
“…22 HID-1 was also found to be an important component of dense core vesicle secretion that controls neuropeptide release. [23][24][25] Interestingly, the response of this mutant to high CO 2 is dose dependent. After exposure to 5% CO 2 , the pumping inhibition is completely rescued and pumping continues at the same rate as under normal atmospheric conditions.…”
Section: Co 2 -Mediated Pumping Inhibition Regulation Is Not Shared Wmentioning
confidence: 92%